2008
DOI: 10.1016/j.jda.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Semi-local longest common subsequences in subquadratic time

Abstract: For two strings a, b of lengths m, n, respectively, the longest common subsequence (LCS) problem consists in comparing a and b by computing the length of their LCS. In this paper, we define a generalisation, called "the all semi-local LCS problem", where each string is compared against all substrings of the other string, and all prefixes of each string are compared against all suffixes of the other string. An explicit representation of the output lengths is of size ((m + n) 2 ). We show that the output can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 17 publications
(34 reference statements)
0
35
0
Order By: Relevance
“…In [60,61], we introduced the semi-local LCS problem, described its connections with unit-Monge matrices and seaweed braids, and gave a number of its algorithmic applications. Many of these applications use distance multiplication of simple unitMonge matrices as a subroutine.…”
Section: Applications In String Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…In [60,61], we introduced the semi-local LCS problem, described its connections with unit-Monge matrices and seaweed braids, and gave a number of its algorithmic applications. Many of these applications use distance multiplication of simple unitMonge matrices as a subroutine.…”
Section: Applications In String Comparisonmentioning
confidence: 99%
“…Motivated by applications to string comparison, we introduced (using different terminology) in [60,61] the following subclass of Monge matrices. A matrix is called unit-Monge, if its density matrix is a permutation matrix; we further restrict our attention to a subclass of simple unit-Monge matrices, which satisfy a straightforward boundary condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same paper, Schmidt showed that IGAPS can be solved in O(Cn 2 ) time. An O(n 2 ) algorithm based on a similar approach for the BGAPS problem was also given by Alves et al [1] and Tiskin [23]. Tiskin [22, p. 60] gave an O(n 2 (log log n/ log n) 2 ) time algorithm for a special case of BGAPS, in which the grid graph corresponds to an LCS problem on two strings.…”
Section: Introductionmentioning
confidence: 98%
“…It has since been studied in several additional papers [1,2,7,[11][12][13][14][15][21][22][23]. Schmidt [21] showed that the GAPS problem can be solved in O(n 2 log n) time.…”
Section: Introductionmentioning
confidence: 99%